Water-Soluble Melanoidin Pigment as a New Antioxidant Component of Fermented Willowherb Leaves (Epilobium angustifolium) - Daniil N. Olennikov; Christina S. Kirillina; Nadezhda K. Chirikova (MDPI AG, 2021)
Willowherb (Epilobium angustifolium L., family Onagraceae) is a well-known food and medicinal plant used after fermentation as a source of beverages with high antioxidant potential. Despite this long history of use, only a few papers have described the chemical profile and bioactivity of fermented willowherb tea in general. To understand the basic metabolic differences of non-fermented and fermented E. angustifolium leaves, we used general chemical analysis, high-performance liquid chromatography with photodiode array detection and electrospray ionization triple quadrupole mass spectrometric detection assay, and an isolation technique. As a result, the content of 14 chemical groups of compounds was compared in the two plant materials; 59 compounds were detected, including 36 new metabolites; and a new water-soluble phenolic polymer of melanoidin nature was isolated and characterized. The fundamental chemical shifts in fermented E. angustifolium leaves relate mainly to the decrease of ellagitannin content, while there is an increase of melanoidin percentage and saving of the antioxidant potential, despite the significant changes detected. The strong antioxidative properties of the new melanoidin were revealed in a series of in vitro bioassays, and a simulated gastrointestinal and colonic digestion model demonstrated the stability of melanoidin and its antioxidant activity. Finally, we concluded that the new melanoidin is a basic antioxidant of the fermented leaves of E. angustifolium, and it can be recommended for additional study as a promising food and medicinal antioxidant agent.